A framework for green project management processes in construction projects. (2016) - Rumaithi, Khaled Hassan Al; Beheiry, Salwa Mamoun
Green industries are growing worldwide and in most cases provide a good rate of return on investment. Moreover, there are many benefits that are associated with green buildings such as lower ecological impact and carbon footprint on the environment, healthier life style for residents and end users, higher service life, less water and energy consumption and less maintenance. The main obstacle for a wide adaptation of green and sustainable buildings in the construction industry is the perceived higher initial costs and the higher risks involved with novel ventures. The higher costs and risks associated with green projects could be reduced by utilising a green project management process that addresses the needs of specific projects. Such green project management processes, if adapted and implemented, could lower the costs and risks of green projects and raise their competitive advantage versus conventional and less efficient projects. This study investigates the conventional project management processes used in the United Arab Emirates (UAE) construction industry and postulates the integration of green practices into these project management processes to enhance their applicability in new construction projects.